Investigation into boron nitride nanoparticle effects on thermal properties of calcium chloride hexahydrate (CaCl2·6H2O) as a phase change material. (12th October 2018) - Barhemmati-Rajab, Nastaran; Zhao, Weihuan
Abstract: Abstract : This paper presents thermal properties' characterization of calcium chloride hexahydrate as a phase change material (PCM) combined with boron nitride nanoparticles (BNNPs), leading to efficient thermal management. BNNPs have high-thermal conductivity up to 200 W/m K. Therefore, the thermal conductivity of PCM could be remarkably enhanced by adding BNNPs to improve the heat transfer performance. In this study, 0.5 wt% of BNNPs were dispersed in the molten PCM. It has been found that the BNNPs could enhance the thermal conductivity of PCM by 71.9%, while reduce the latent heat of fusion and specific heat of PCM by 11.1% and 60.9%, respectively.